Create, compose, connect! : reading, writing, and learning with digital tools - Hyler, Jeremy; Hicks, Troy (New York : Routledge, 2014)
'Find out how to incorporate digital tools into your English language arts class to improve students' reading, writing, listening, and speaking skills. Authors Jeremy Hyler and Troy Hicks show you that technology is not just about making a lesson engaging; it's about helping students become effective creators and consumers of information in today's fast-paced world. You'll learn how to use mobile technologies to teach narrative, informational, and argument writing as well as visual literacy and multimodal research. Each chapter is filled with exciting lesson plans and tech tool suggestions that you can take back to your own classroom immediately'-- Provided by publisher.
1. Create, compose, connect! -- 2. Building a classroom (and virtual) community -- 3. The rest of the story: Reading and writing narratives -- 4. Reading our world, writing our future (Informational) -- 5. Looking for evidence (Argumentative) -- 6. Can you hear me now? (Speaking and listening) -- 7. Seeing isn't always believing (Visual literary) -- 8. Our many voices (Multigenre research project).
Includes bibliographical references (pages 177-183).
Keywords: English language -- Study and teaching -- Computer-assisted instruction; Language arts -- Computer-assisted instruction; Computers and literacy; Creative writing -- Computer-assisted instruction; Educational technology